Bio-ethological researches on the Hymenoptera of the biocenosis of Phyllonorycter robiniellus (Clemens) (Lepidoptera Gracillariidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
In the biocenosis of Phyllonorycter robiniellus (Clemens) checked in Piedmont (northwestern Italy), 16 Hymenoptera (Ichneumonidae, Braconidae, Chalcididae, Pteromalidae, Eulophidae) were found. Of these, 6 were parasitoids, 3 were hyperparasitoids, 7 revealed a behaviour both as parasitoids and hyperparasitoids. In the considered area the parasitization was over 60% and was caused above all by the braconid Pholetesor bicolor (Nees) and the eulophids Baryscapus nigroviolaceus (Nees) and Minotetrastichus frontalis (Nees). This last species was always found among the natural enemies of the microlepidoptera Parectopa robiniella Clemens, Stigmella malella (Stainton), Leucoptera malifoliella Costa, Phyllonorycter blancardellus (Fabricius). Data on biology and ethology of the above 16 species of Hymenoptera are given.
Keywords: microlepidoptera; parassitoids; hyperparasitoids; Robinia pseudacacia